Optimizing the development and utilization of libraries through collaboration - Fitriani Pratama, Anandita; Rohman, Asep Saeful; Hashim, Hasnah (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2023)
Background of the study: Collaboration in the library sector is essential to fulfill the library users' information needs. Purpose: The objective of this study is to investigate the methods, types of collaboration, and challenges involved in the implementation of cooperative efforts between the West Java Dispusipda and UNIKOM Library, to enhance the development and utilization of the library. Method: In this research, a qualitative approach is employed to analyze the data, which is subsequently processed through the stages of data reduction, data presentation, and drawing conclusions. Findings: The collaboration between the West Java Dispusipda and UNIKOM Library is based on a policy that outlines the roles, responsibilities, and scope of the cooperation. The agreed activity plan includes various initiatives such as enhancing the quality of human resources, exchanging experts, conducting research cooperation, implementing science and technology applications, and collaborating in other areas. However, due to the Covid-19 pandemic, not all planned activities have been fully implemented. One notable achievement is the accreditation of the UNIKOM Library. Conclusion: Cooperation is an effort to achieve library goals